2019
DOI: 10.1590/s2175-97902019000117240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iguratimod on diclofenac metabolism by CYP2C9 in rats and human recombinant CYP2C9 yeast cells

Abstract: Iguratimod (IGU, also known as T-614), a novel disease modifying antirheumatic drug intended to cure patients with rheumatoid arthritis (RA). The purpose of this study is to evaluate the effect of IGU on the pharmacokinetics of CYP2C9 probe drug diclofenac and its metabolite 4′-hydroxy diclofenac in vivo and in vitro. In in vivo experiments, 24 rats were randomly assigned to three groups consisting of the control group (Normal saline), low dose IGU group (10 mg/kg) and high dose IGU group (30 mg/ kg). Blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…These metabolites are 3′-hydroxydiclofenac, 4′-hydroxydiclofenac, 5′-hydroxydiclofenac, and 3′-hydroxy-4′-methoxydiclofenac [ 9 ]. A previous paper showed that diclofenac is metabolized to 4′-hydroxydiclofenac and 5′-hydroxydiclofenac in rat liver microsomes, whereas in human liver microsomes, it metabolized to only 4′-hydroxydiclofenac [ 10 ]. The metabolite 5′-hydroxydiclofenac is formed predominantly by the CYP3A4 enzyme and by CYP2C19, CYP2C8, and CYP2C18 to a lesser extent [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These metabolites are 3′-hydroxydiclofenac, 4′-hydroxydiclofenac, 5′-hydroxydiclofenac, and 3′-hydroxy-4′-methoxydiclofenac [ 9 ]. A previous paper showed that diclofenac is metabolized to 4′-hydroxydiclofenac and 5′-hydroxydiclofenac in rat liver microsomes, whereas in human liver microsomes, it metabolized to only 4′-hydroxydiclofenac [ 10 ]. The metabolite 5′-hydroxydiclofenac is formed predominantly by the CYP3A4 enzyme and by CYP2C19, CYP2C8, and CYP2C18 to a lesser extent [ 6 ].…”
Section: Introductionmentioning
confidence: 99%